Infrared and far-infrared spectroscopy of (CH3OH)-C-13: TeraHertz laser lines and assignments - Costa, L. F. L.; Moraes, João Carlos Silos [UNESP]; Cruz, F. C.; Viscovini, R. C.; Pereira, D. (Elsevier B.V., 2007)
We use a (CO2)-C-13 laser as optical pumping source to search for new THz laser lines generated from (CH3OH)-C-13. Nineteen new THz laser lines (also identified as far-infrared, FIR) ranging from 42.3 mu m (7.1 THz) to 717.7 mu m (0.42 THz) are reported. They are characterized in wavelength, offset, relative polarization, relative intensity, and optimum working pressure. We have assigned eight laser lines to specific rotational energy levels in the excited state associated with the C-O stretching mode. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: assignments; (CH3OH)-C-13; far-infrared lasers; TeraHertz lasers